2013
DOI: 10.1016/j.celrep.2013.03.037
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Cluster miR-17-92 Regulates Neural Stem Cell Expansion and Transition to Intermediate Progenitors in the Developing Mouse Neocortex

Abstract: SUMMARY During development of the embryonic neocortex, tightly regulated expansion of neural stem cells (NSCs) and their transition to intermediate progenitors (IPs) are critical for normal cortical formation and function. Molecular mechanisms that regulate NSC expansion and transition remain unclear. Here, we demonstrate that the microRNA (miRNA) miR-17-92 cluster is required for maintaining proper populations of cortical radial glial cells (RGCs) and IPs through repression of Pten and Tbr2 protein. Knockout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(168 citation statements)
references
References 39 publications
(46 reference statements)
7
156
1
3
Order By: Relevance
“…A recent study of the functions of the miR-17-92 cluster has shown that miR-19 and miR-92a repress PTEN and Tbr2 (also known as Eomes), respectively, and suppress the transition from radial glial cells to intermediate progenitors (24). These two miRNAs have strong oncogenic effects by regulating PTEN and Bim (also known as Bcl2l11) (6,23).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of the functions of the miR-17-92 cluster has shown that miR-19 and miR-92a repress PTEN and Tbr2 (also known as Eomes), respectively, and suppress the transition from radial glial cells to intermediate progenitors (24). These two miRNAs have strong oncogenic effects by regulating PTEN and Bim (also known as Bcl2l11) (6,23).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although not directly affecting the self-renewal capacity of radial glial cells (RGCs) within the developing cerebral cortex, Eomes is a key determinant of the differentiation of intermediate progenitor cells (IPCs), which comprise the RGC daughter transit amplifying progenitor population (Arnold et al, 2008b;Sessa et al, 2008). The transition from NSC to IPC is regulated by miR-92a through post-transcriptional regulation of Eomes (Bian et al, 2013). Eomes is also a crucial regulator of granule cell formation from NSCs in the dentate gyrus, both during development and in the adult.…”
Section: T-box Genes and Stem Cell Biologymentioning
confidence: 99%
“…97 In the development of mouse neurocortex, the miR17-92 cluster controls neural progenitor cell proliferation by suppressing phosphatase and tensin homolog deleted on chromosome 10 (PTEN) and the transcription factor Tbr 2. 98,99 Ablation of the miR17-92 cluster in OPCs during brain development reduces their proliferation, indicating that this cluster affects oligodendrogenesis. 100 Stroke robustly increases miR17-92 cluster expression in V/SVZ neural progenitor cells.…”
Section: Micrornas and Signaling Pathwaysmentioning
confidence: 99%